Analyse cout-efficacite des interventions pour reduire les maladies diarrheiques chez les consommateurs de laitues irriguees avec des eaux usees au Ghana. In French. [Cost-effectiveness analysis of interventions for diarrhoeal disease reduction among consumers of wastewater-irrigated lettuce in Ghana] - Seidu, R.; Drechsel, Pay (2011)
Interventions proposed and implemented for the mitigation of diarrhoeal diseases associated with wastewater reuse in agriculture have received little, if any, comparative assessment of their cost-effectiveness. This chapter assesses the costs, outcomes and cost-effectiveness of the so-called ?treatment? and ?non- or post-treatment? interventions as well as a combination of these for wastewater irrigation in urban Ghana using an approach that integrates quantitative microbial risk assessment (QMRA), disability-adjusted life years (DALYs) and cost-effectiveness analysis (CEA). The cost-effectiveness ratios (CERs) for the treatment and non-treatment interventions assessed ranged from US$31/DALY to US$812/DALY averted. Risk-reduction measures targeting farming practices and the basic rehabilitation of local wastewater treatment plants were the most attractive interventions with a CER well below the threshold of US$150/DALY, sometimes considered as the upper limit for a health intervention to be cost-effective in developing countries. All combinations associated with the basic rehabilitation of the treatment plants, with either on-farm or post-harvest interventions or both, resulted in CERs within the range of US$40/DALY to US$57/DALY. However, the CERs for the construction of a new wastewater treatment plant either as an independent intervention or in combination with on-farm and post-harvest interventions were unattractive in view of health-risk reduction for wastewater irrigation. Although attractive, the CERs of non-treatment options are largely dependent on compliance (adoption) by farmers and food vendors. In this regard, the CER increased by almost fivefold when the adoption rate was only 25 per cent by farmers and food vendors; but was attractive as long as adoption rates did not fall below 70 per cent. On the other hand, the success of the treatment option depends on the functionality of the treatment plants which is not without challenges in a country like Ghana. Thus, this chapter stresses the need for a balanced risk-management approach through a combination of treatment and non-treatment interventions to hedge against failures that may affect CERs at any end. While this chapter provides a contribution to the debate on interventions for health-risk mitigation in wastewater irrigation, more case studies would be useful to verify the data presented here.